WATER QUALITY MONITORING OF THE ARIAKE SEA BY REMOTE SENSING AND UTILIZATION OF FIELD OBSERVATION - K. Ohgushi; H. AR; T. Y. Gan (Lowland Technology International, 2004)
A remote sensing is one of the most powerful solution for estimating water quality in wide water bodies effectively. The earth observation stellites Landsat have been observing the land and ocean from space for a long time with consistent specification plus new additional technology. In this paper, a water quality in the Ariake Sea, Japan is estimated by using Landsat-TM nad ETM+ images with field observation. The models for water salinity and cholorophyll-a concentration are developed by regression analysis like the transparancy and water temperature models, and they are also validated by other observed data. In order to understand characteristic of water quality in the Ariake Sea. a continuous observation was also executed at a fixed observation tower in the bay for about five months. A GIS technique was also applied to consider spatial and seasonal characteristic of water environment of this bay.